P358Safety of intracoronary delivery of mesenchymal/stromal stem cells: insights from coronary microcirculation invasive assessment. (15th July 2014) - Fiarresga, A; Lobato Da Silva, C; Cavaco-Goncalves, S; Selas, M; Simoes, I; Oliveira, E; Carrapico, B; Cardim, N; Sampaio Cabral, J; Cruz Ferreira, R
Abstract: Mesenchymal/stromal stem cells (MSC) have unique properties favorable to their future use in clinical practice and have been studied for cardiac repair. MSC are larger than coronary microvessels and there is controversy about the risk of embolization and microinfarctions, which could compromise the intracoronary route for their delivery. The index of microcirculatory resistance (IMR) is an invasive method for quantitatively assessing the coronary microcirculation status and could be applied for evaluation of the acute effects of MSC intracoronary infusion providing new insights for this open question. Our purpose was to examine heart microcirculation effects after MSC intracoronary injection with IMR. Methods and Results: Eighteen healthy swine were randomized to receive 30 x 106 MSC or saline by intracoronary infusion. In the heart catheterization laboratory hemodynamic, electrocardiographic and coronary flow parameters were monitored and there were no differences between groups. Thermodilution-derived coronary flow reserve (CFR) and IMR were assessed at baseline, 5 and 30 minutes post-delivery using a coronary pressure wire. CFR had a small although not significant decrease in animals receiving MSC. After cell infusion, IMR increased at 5 and 30 minutes with a significant difference from the control group at 30 minutes (Table). Conclusion: Intracoronary delivery of MSC is possible without a significant negative impact on hemodynamic parameters, electrical stability and epicardial coronary flow status. However, this study provides definitive evidence of microcirculatory disruption upon intracoronary administration of MSC, in a large animal model closely resembling human cardiac physiology, function and anatomy. CFR and IMR mean values CONTROL MSC p Baseline CFR 3.8 ± 1 4 ± 2 0.7 Baseline IMR (U) 8.1 ± 1 6.7 ± 0.6 0.3 Post-delivery CFR - 5 min. 3.6 ± 1 3 ± 2 0.5 Post-delivery CFR - 30 min. 3.8 ± 2 2.3 ± 1.5 0.064 Post-delivery IMR - 5 min. (U) 9.8 ± 1 15.3 ± 2.8 0.08 Post-delivery IMR - 30 min. (U) 8.8 ± 1 13.2 ± 1.8 0.02 Coronary flow reserve (CFR), index of microcirculatory resistance (IMR)